Pengaruh Ekonomi Makro Terhadap Harga Saham di-intervening Profitabilitas Pada JII Periode 2019-2021 - Faisal Dwi Putra; Veny Puspita; Sintia Safrianti (Forum Kerjasama Pendidikan Tinggi, 2023)
Referring to demographic data, Indonesia's Muslim population currently reaches 229.62 million of Indonesia's total population of 269.6 million, the presence of sharia stocks is certainly an important matter to discuss. There are several Islamic stock indices in Indonesia, one of which is the Jakarta Islamic Index (JII). The purpose of the birth of the Jakarta Islamic Index (JII) is to increase investor confidence, especially Muslim investors, in the shares of companies whose company activities run according to Islamic sharia. Inflation, exchange rates and interest rates are one of the macroeconomic variables that can generally affect stock prices, then profitability is added as an intervening variable. This research is sourced from secondary data obtained from stock exchange sites, Indonesian banks and various other reliable sources. The research method used is the sem-pls method with smartpls 4.0 software to measure the influence of variables either directly or indirectly. Based on the results of the analysis it was found that inflation, exchange rates and interest rates did not have a significant direct effect on stock prices while profitability had a significant direct effect on stock prices, then for a direct effect on profitability it was found that inflation and interest rates had a significant effect on profitability while the exchange rate no effect on profitability. For the indirect effect through the intervening variable, it was found that interest rates have a significant effect on stock prices after being intervened by company profits, while inflation and exchange rates have no significant effect on stock prices after being intervened by company profits.